The influence of the injectors with swirling flow generating on the heat transfer in the concentric heat exchanger - Cakmak, Gulsah; Yidiz, Cengiz (Pergamon-Elsevier Science Ltd, 2007)
In this paper, undertaken to enhance heat transfer rates, swirling motion was imposed on the hot air by placing injectors with various diameters and numbers in triangle line rows on the entrance section of the inner pipe of the concentric heat exchanger. With this aim various the injectors were prepared to test in the experiments. These elements can be placed and removed easily on the entrance section of the inner pipe. The experiments were carried out for counter current flow models of the fluids at different Reynolds numbers. The heat transfer rates increased with decreasing diameter and with increasing number of the injectors used in the experiments. The results showed that up to 93% enhancements could be accomplished in heat transfer rates with this kind of swirl generators compared to heat exchanger without these elements. In the end of the study, the results showed that a rather smaller size but the same capacity heat exchanger could be proposed by using these elements imposing Swirling to the fluid flowing through inner pipe. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: heat exchanger; swirling flow; injectors